Neoliberal natures. Conflicts around urban-real estate extractivism, coordinated by Patricia Pintos and Sofía Astelarra (coords.), (2023). Editorial El Colectivo - Manzanelli, Macarena Del Pilar (2025)
The book Naturalezas neoliberales. Conflictos en torno al extractivismo urbano-inmobiliario, coordinated by Patricia Pintos and Sofia Astelarra (2023), is reviewed. It maps contemporary practices of urban-real estate extractivism and the resistance of vulnerable populations in an interdisciplinary way. Its contribution consists of providing conceptual tools about models of capital accumulation and neoliberal practices; generating diagnoses for the monitoring of urban-environmental real estate conflicts; and highlighting the potential and political creativity of local.